Advancements in Microextraction by Packed Sorbent: Insights into Sorbent Phases and Automation Strategies - Rafael Oliveira Martins; João Victor Basolli Borsatto; Camila Will; Fernando Mauro Lanças (Separations)
Miniaturized solid-based approaches have added an eco-friendly dimension to analytical procedures, establishing themselves as promising strategies for a wide range of applications. Among these, microextraction by packed sorbent (MEPS) stands out due to its ability to facilitate efficient sample interaction with a densely packed sorb ent phase within the microextraction system. MEPS offers several advantages, including preconcentration capabilities and the use of minimal sample and solvent volumes, making it an appealing choice for modern analytical workflows. Since the extraction efficiency is largely dictated by the sorbent phase, recent advancements in sorbent design have garnered considerable attention in the field of sample preparation. Innovations in sorbent phases have not only enhanced the MEPS efficiency but also enabled the development of semi- and fully automated systems, paving the way for high-throughput methodologies. These advancements have elevated MEPS beyond traditional offline miniaturized sample preparation methods, offering new opportunities for streamlined and scalable analyses. Therefore, this study provides a comprehensive overview of novel sorbent phases used in MEPS, with a particular focus on both bio-based and synthetic materials. Furthermore, it explores the semi- and fully automated aspects of MEPS, highlighting current trends, technological advancements, and future directions in this rapidly evolving field.